Sanksi Pengembalian Kerugian Keuangan Negara Bagi Koruptor Berdasarkan Asas Lex Specialis Sistematis: Penalties for the Restitution of Financial Losses to the State Imposed on Corrupt Officials Based on the Principle of Systematic Lex Specialis - Wilda Amalia (SIYASI: Jurnal Trias Politica, 2023)
The issue of corruption in Indonesia has become a very tough problem to eradicate. A culture that has been rooted from generation to generation where state financial losses are dredged up. Various programs are created in the name of people's welfare but in fact create opportunities for personal enrichment. So far, sanctions for corruptors have not found a bright spot in creating clean institutions and countries. Starting from prison sanctions, to impoverishing corruptors still gives doubts whether the purpose of punishment to provide a deterrent effect has been realized. So that then raises another option whether the sanction of returning state financial losses can bring more benefits or still not. Departing from this, this article aims to examine more deeply the element of state financial losses in corruption cases by looking at the judges' considerations in deciding corruption cases. Then by examining and trying to construct the principle of lex specialist systematic as a legal reference in determining the verdict of returning state financial losses for perpetrators of corruption.